Linkages between poverty and land management in rural Uganda: evidence from the Uganda National Household Survey, 1999/00 - Pender, John L.; Ssewanyana, Sarah; Kato, Edward; Nkonya, Ephraim M. (International Food Policy Research Institute, 2004)
This study investigates the impacts of rural poverty on farmers’ land management decisions, crop production and incomes, based upon analysis of data from the 1999/2000 Uganda National Household Survey. We find that the impacts of rural poverty on land management, crop production and income depend upon the type of poverty (i.e., what asset or access factor is constrained) and the type of land management considered...Our results suggest that improvement in smallholders’ access to land, other assets, education, extension, market information, credit, roads, and off-farm opportunities can help to break the downward cycle of poverty and land degradation, and put farmers on a more sustainable development pathway. Access to land (area and quality), other assets, education and off-farm opportunities appear to be particularly important in addressing poverty directly, while other interventions are likely to have more indirect impacts, as they influence land management, crop choice, and other livelihood decisions. Given the importance of land as the major asset owned by poor rural households in Uganda, investing in land quality maintenance and improvement is a critical need. However, we found low marginal returns to investments in organic or inorganic fertilizer and other land management practices, suggesting that it will be difficult to get farmers to make such investments in the present environment. Improvements in the market environment as well as development of more profitable land management technologies appears essential to address this need."--from Authors' Abstract